Developing Smart Comic as Reading Media of Tenth Grade Students of SMA Muhammadiyah Pangkalpinang - Nur Rifki, Iqbal; Indra Aprilliandari, Dwi; Haiyudi (Jurnal Ilmiah Pendidik Indonesia, 2024)
The development of smart comic media was motivated by the problems experienced by teachers and students at SMA Muhammadiyah Pangkalpinang. The problems that arise come from two points of view: the student’s point of view and the teacher’s point of view. According to students, the main problem that arises is boredom when learning English in class, and based on the teacher’s point of view, that is, teachers still use textbooks or LKS (Lembar Kerja Siswa), so that English learning media is still lacking. So, a solution is needed to overcome this problem in the form of smart comics so that they can attract students’ interest and help teachers in teaching. The aim of this research is to develop intelligent comic products that are appropriate and effective in teaching narrative text to high school students. The method used in this research is research and development with the ADDIE development model, which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The validation results of the product being developed were declared & “very feasible” to be tested by validators, with the results of the first validator being 79.54% and the results of the second validator being 82.95%, while the test results of the product being developed were 82.95%. declared & “very good” with teacher response test results of 98.43% and student response test results of 91.33%..